UMPSA ranks 601-800 in the world in THE WUR 2024 - Mimi Rabita, Abd Wahit (UMPSA, 2023)
PEKAN, 28 September 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has been listed in the 601-800 position range globally in the Times Higher Education World University Rankings 2024 (THE WUR), which was recently announced.